Improving transient state myoelectric signal recognition in hand movement classification using gyroscopes - Boschmann, Alexander; Nofen, Barbara; Platzner, Marco (Proc. IEEE Int. Conf. Eng. Med. Biolog. (EMBC))

Reducing the limb position effect in pattern recognition based myoelectric control using a high density electrode array - Boschmann, Alexander; Platzner, Marco (Proc. IEEE ISSNIP Biosignals and Biorobotics Conference (BRC))

Investigating Evolvable Hardware Classification for the BioSleeve Electromyographic Interface - Glette, Kyrre; Kaufmann, Paul; Assad, Christopher; Wolf, Michael (IEEE Intl. Conf. on Evolvable Systems (ICES))

Adapting Hardware Systems by Means of Multi-Objective Evolution - Kaufmann, Paul

Classification of Electromyographic Signals: Comparing Evolvable Hardware to Conventional Classifiers - Kaufmann, Paul; Glette, Kyrre; Gruber, Tiemo; Platzner, Marco; Torresen, Jim; Sick, Bernhard (IEEE Transactions on Evolutionary Computation)

Behavior Models for Electric Vehicles - Knoop, Michael

Verbesserung der Erkennungsrate eines Systems zur Klassifikation von EMG-Signalen durch den Einsatz eines hybriden Lagesensors - Nofen, Barbara

Überquerung der Styx - Betriebsparametervariation und Fehlerverhalten eines Platform FPGAs - Pudelko, Daniel

Identifikation und Wiederherstellung von kryptographischen Schlüsseln mit FPGAs - Riebler, Heinrich

MiBenchHybrid : Erweiterung eines Benchmarks um Hardwarebeschleunigung - Sprenger, Alexander

Beschleunigung von Einzelbild-Erkennungsverfahren auf Datenfluss basierenden HPC Systemen - Steppeler, Philipp

Real-Time Simulation of Distribution Grids with high Penetration of Regenerative and Distributed Generation - Toebermann, Christian; Geibel, Daniel; Hau, Manuel; Brandl, Ron; Kaufmann, Paul; Ma, Chenjie; Braun, Martin; Degner, Tobias (Real-Time Conference)

A fast TCAD-based methodology for Variation analysis of emerging nano-devices - Ghasemzadeh Mohammadi, Hassan; Gaillardon, Pierre-Emmanuel; Yazdani, Majid; De Micheli, Giovanni (2013 IEEE International Symposium on Defect and Fault Tolerance in VLSI and Nanotechnology Systems (DFTS))

Vertically-stacked silicon nanowire transistors with controllable polarity: A robustness study - Gaillardon, Pierre-Emmanuel; Ghasemzadeh Mohammadi, Hassan; De Micheli, Giovanni (2013 14th Latin American Test Workshop-LATW)

Schema-based Parallel Compression and Decompression of XML Data - Böttcher, Stefan; Feldotto, Matthias; Hartel, Rita (WEBIST 2013 - Proceedings of the 9th International Conference on Web Information Systems and Technologies, Aachen, Germany, 8-10 May, 2013)
Whenever huge amounts of XML data have to be transferred from a web server to multiple clients, the transferred data volumes can be reduced significantly by sending compressed XML instead of plain XML. Whenever applications require querying a compressed XML format and XML compression or decompression time is a bottleneck, parallel XML compression and parallel decompression may be of significant advantage. We choose the XML compressor XSDS as starting point for our new approach to parallel compression and parallel decompression of XML documents for the following reasons. First, XSDS generally reaches stronger compression ratios than other compressors like gzip, bzip2, and XMill. Second, in contrast to these compressors, XSDS not only supports XPath queries on compressed XML data, but also XPath queries can be evaluated on XSDS compressed data even faster than on uncompressed XML. We propose a String-search-based parsing approach to parallelize XML compression with XSDS, and we show that we can speed-up the compression of XML documents by a factor of 1.4 and that we can speed-up the decompression time even by a factor of up to 7 on a quad-core processor.

Decoding IEEE 802.11a/g/p OFDM in software using GNU radio - Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Dressler, Falko (Proceedings of the 19th annual international conference on Mobile computing & networking - MobiCom '13)

An IEEE 802.11a/g/p OFDM receiver for GNU radio - Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Dressler, Falko (Proceedings of the second workshop on Software radio implementation forum - SRIF '13)

To crash or not to crash: Estimating its likelihood and potentials of beacon-based IVC systems - Joerer, Stefan; Segata, Michele; Bloessl, Bastian; Cigno, Renato Lo; Sommer, Christoph; Dressler, Falko (2012 IEEE Vehicular Networking Conference (VNC))

A Vehicular Networking Perspective on Estimating Vehicle Collision Probability at Intersections - Joerer, Stefan; Segata, Michele; Bloessl, Bastian; Lo Cigno, Renato; Sommer, Christoph; Dressler, Falko (IEEE Transactions on Vehicular Technology)

Use both lanes: Multi-channel beaconing for message dissemination in vehicular networks - Klingler, Florian; Dressler, Falko; Cao, Jiannong; Sommer, Christoph (2013 10th Annual Conference on Wireless On-demand Network Systems and Services (WONS))